Drawing the Impossible - Luke Tipene (Cubic Journal, 2018)
This pictorial essay reflects on a unique category of architectural drawing that depicts spaces that cannot physically exist. It suggests that this specific mode of drawing plays a significant role in the production of meaning in social space through depicting ephemeral characteristics of our social relations. This argument is discussed in relation to Michel Foucault’s theoretical allegory of the heterotopic mirror, and illustrated through accompanying images of the drawing project The Virtual Relations (2009). This project used the methodology of “drawing the impossible” with Henri Lefebvre’s theory for the production of space to explore ephemeral conditions of social interaction in the domestic interior as five spatial descriptions.